The Nāṭyaśāstra text and its influence on Hindu religious art in Indonesia - Devi, Jyothi; Krishnanandayani (Life and Death: Journal of Eschatology, 2024)
This research examines the influence of the Nāṭyaśāstra, a classic text of Indian literature that focuses on the performing arts, on Hindu religious arts in Indonesia. Through an in-depth analysis of the implementation of the Nāṭyaśāstra in Hindu religious arts, this study aims to understand how this classical text plays a role in shaping and maintaining the heritage of religious arts in the Indonesian context. It is found that the Nāṭyaśāstra not only serves as a guide for artists and performers, but also influences the structure, style, and content of various Hindu religious performances in Indonesia. The principles of Nāṭyaśāstra, such as rasa (taste), aesthetics (bhava), and performance techniques, emerged as key elements in the creation and performance of religious performing arts. This research also highlights the successful adaptation and integration of local cultural elements by Hindu communities in Indonesia in the application of Nāṭyaśāstra. The results confirm that the Nāṭyaśāstra is not only the foundation but also the source of inspiration for Hindu religious art in Indonesia. The integration of local culture is not a mere reproduction, but a creative response to the social and cultural environment. This phenomenon reflects the sustainability and ongoing life of Hindu religious art, affirming religious identity while creating a unique and authentic art form. As such, this research provides a deeper understanding of the role of Nāṭyaśāstra in nurturing and enriching Hindu religious art in Indonesia. The results can contribute to the preservation of cultural heritage, cross-cultural understanding, and enrich insights into the relationship between Indian classical texts and religious art expressions in local Indonesian contexts